Estratégia ambiental e agências de viagens e turismo :um estudo sobre a importância de práticas ambientais na escolha de um pacote turístico - Câmara, Michele Galdino (2006)
The objective of the work was to investigate, from the vision of travel agents, the importance of environmental practices as a decision factor in the purchase of a tourist package. For in such a way, it was established as target population, the travel agencies and tourism linked to he Brazilian Association of Travel agencies ABAV, hearing the Brazilian travel agents that exerted the function in Natal, city in 2005. The election of the sample was accomplished using the simple random sampling technique. The amount of agents effectively searched was of 150 agents being distributed 150 questionnaires, with closed and opened questions, applied during the month of November in 2005. Results showed great variability of interviewed answers in that if it relates for sale of package tourist where the customer demonstrates enviromental concern with the environmental quality. Through multiple regression analyses, it was environmental concern with the environmental quality of the place and the perception of the practical importance of the existence environmental practices in the place as important factor in the decision of tourist package purchase